2020
DOI: 10.3390/ani10030533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Meal Substitution by Raw Chickpea Seeds on Thermal Properties and Fatty Acid Composition of Subcutaneous Fat Tissue of Broiler Chickens

Abstract: Simple Summary: A soybean meal, commonly used as a primary source of protein in animal diets, is often obtained from processing genetically modified soybean varieties. The tendency to reduce the use of feeds containing transgenic constituents increases the need for alternative sources of dietary protein. In this study, we fed broiler chickens diets containing either soybean meal or raw chickpea seeds. We examined the effect of such a substitution on broilers' subcutaneous fat tissue, which has numerous importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
(88 reference statements)
0
13
0
1
Order By: Relevance
“…A possibility of partial substitution of SBM is ascribed to the use of legume seeds. In addition to raw or processed pea, lupine, or horse bean seeds [ 9 , 10 , 11 ], which have been investigated to assess their suitability for use in animal nutrition, the chickpea ( Cicer arietinum L.) [ 12 , 13 , 14 , 15 ] deserves attention. The plant is not very common in Poland, but is one of the most important legumes in the world [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possibility of partial substitution of SBM is ascribed to the use of legume seeds. In addition to raw or processed pea, lupine, or horse bean seeds [ 9 , 10 , 11 ], which have been investigated to assess their suitability for use in animal nutrition, the chickpea ( Cicer arietinum L.) [ 12 , 13 , 14 , 15 ] deserves attention. The plant is not very common in Poland, but is one of the most important legumes in the world [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the soybean production in the world consists of genetically modified soybeans and its use in human and/or animal nutrition is planned to be banned in many countries. Therefore, the need for alternative protein sources such as lupine, chickpea, faba bean, and insect meal is increasing day by day [1][2][3][4]. The high price of soybean meal increases the importance of sunflower meal (SFM), which is one of the most produced oilseed meal in our country, as an alternative protein source to soybean meal [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of FB is on the increase due to the high cost of importing SBM in areas where it is not naturally grown. Furthermore, SBM is often obtained from genetically modified soybean cultivars, which is a concern for consumers and is not suitable for organic production thus, raising the need for alternatives in animal nutrition [ 69 , 70 ]. Faba beans are known to be high in ANF such as tannins, vicine, lectins, protease inhibitors, and convicine [ 6 , 31 ], which negatively impacts the growth performance and nutrient utilization of pigs and broiler chickens [ 6 , 71 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%
“…Brenes et al [ 90 ] reported improvements in protein and fat digestibility when broiler chickens were fed extruded CKP. Paszkiewicz et al [ 69 ] reported a reduction in saturated fatty acids and an increase in the unsaturated fatty acids composition of the subcutaneous fat in broiler chickens when CKP was included in broiler chicken diets. It has been suggested that CKP can be included in diets of weaning pigs at 15% [ 16 ], finishing pigs at 30% [ 15 , 38 ], and broiler chickens at 12–15% [ 39 , 89 ].…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%